2022
DOI: 10.1037/cap0000305
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Canadians’ experiences of the dual pandemics of COVID-19 and racism: Implications for identity, negative emotion, and anti-racism incident reporting.

Abstract: Many Chinese Canadians (CCs) have experienced increased racism and xenophobia since the beginning of the Coronavirus disease (COVID-19) pandemic. This study focused on how this rise of anti-Chinese discrimination, in addition to the threats posed by the pandemic itself, affects not only CCs’ well-being, but also their Chinese and Canadian identities. We surveyed 874 CC adults from across Canada, M age = 42.09; 47.7% females; 628 foreign-born, first-generation (G1) and 246 Canadian-born, second or later generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 113 publications
0
22
0
1
Order By: Relevance
“…8 In line with earlier research, we found that, although Canada prides itself on being a multicultural country, discrimination against Asian Canadians has been common during the pandemic, and Sinophobia during this time may not be simply because of the racialization of the virus (e.g., Chinese virus) but also a result of historical anti-Asian racism. 35 Previous research has found that racially stigmatized people experience a high rate of physical, psychological and social illnesses and impairments. 36 We found that the threat of discrimination contributed to participants' mental exhaustion and feelings of unsafety.…”
Section: Discussionmentioning
confidence: 99%
“…8 In line with earlier research, we found that, although Canada prides itself on being a multicultural country, discrimination against Asian Canadians has been common during the pandemic, and Sinophobia during this time may not be simply because of the racialization of the virus (e.g., Chinese virus) but also a result of historical anti-Asian racism. 35 Previous research has found that racially stigmatized people experience a high rate of physical, psychological and social illnesses and impairments. 36 We found that the threat of discrimination contributed to participants' mental exhaustion and feelings of unsafety.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian Institutes of Health Research has four funded papers on this topic with 252 citations. The funded papers were on the topic of financial and psychological impact to mothers and children during COVID-19 ( Letourneau et al, 2021 ); Chinese Canadians’ experience during pandemic ( Lou et al, 2021 ); and related to sleep-related issues and psychological impacts during COVID-19 ( Morin et al, 2020 , 2022 ). The pandemic opened new areas for the researcher to work upon the goals of the human community.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, queer folk across the country were organizing in response to the discrimination and support needs of those impacted by AIDS/HIV. As with the COVID-related scapegoating and violence currently directed toward people of Asian descent, the scapegoating and violence directed toward gay men during the early years of the AIDS epidemic was ever-present ( Lou et al, 2021 ; Rosenfeld et al, 2012 ; Shepard, 2009 ). Consequently, my work on the peer support phone line also included the provision of AIDS/HIV information and support.…”
Section: Reflectionsmentioning
confidence: 99%
“…À cette époque, les queers de partout au pays s’organisaient en réponse à la discrimination et à la nécessité de soutenir les personnes touchées par le sida et le VIH. La désignation des homosexuels comme boucs émissaires et la violence à leur encontre étaient omniprésentes au cours des premières années de l’épidémie de sida, comme le sont aujourd’hui la désignation de boucs émissaires et la violence à l’égard des personnes d’origine asiatique en lien avec la COVID ( Lou et al, 2021 ; Rosenfeld et al, 2012 ; Shepard, 2009 ). Par conséquent, mon travail pour la ligne d’entraide comprenait également l’offre d’information et de soutien sur le sida et le VIH.…”
Section: Réflexionsunclassified